Complementary contribution of parents and therapists in the assessment process of children. Issue 6 (4th June 2013) - Rosenberg, Limor; Bart, Orit; Ratzon, Navah Z.; Jarus, Tal
<x xml:space="preserve">Abstract</x> Background/aim Traditional developmental models assume that the underlying capacities of children contribute to their participation. In this framework, preschoolers who are referred for occupational therapy services usually undergo an assessment intended to identify capacities in certain domains. Contrary to this, newer ecological models assume that child participation is a consequence of a multidimensional interaction between personal and environmental factors. As a result clinicians are increasingly focusing their assessment on performance and participation. This study aimed to assess the correlation between children's performance skills, their capacities and participation; and to explore whether parents' observations, alongside therapist observations and standardised assessments, contribute to an enhanced understanding of child participation. Method Participants included 188 parents and their children, aged 4–6 years, with and without mild developmental difficulties. Data were collected using standardised assessments for child capacities, and questionnaires completed by parents and occupational therapists regarding child participation and performance skills. Results Significant correlations were found between parent assessments of child performance skills and child participation, but not with child capacities. The opposite was found to be true for occupational therapist assessments of child performance skills which were found to correlate with child capacities, but not with participation. Additionally, an interaction effect was found for both groups. Occupational therapists reported higher performance skills as compared to parents, but the difference was only significant for children without mild difficulties. Conclusion As suggested by ecological models of child participation, the findings highlight the importance of parent‐therapist collaboration in the assessment process of children.